ANALISIS PENGARUH KEBUDAYAAN, SOSIAL, PRIBADI DAN PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN (Pada Wisatawan Museum Angkut, Kota Batu) - Mariana, Dinda Rindi Putri; Ayuni, Risca Fitri (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims to determine the influence of cultural , social , personal , and psychological to the decision visit the Transport Museum , Batu . This type of research  is explanatory research . The data collection of this study using a questionnaire . The study population were tourists Museum of Transport . Samples were people who had never  visited the Museum Angkut of one or more than one time . The sampling technique was conducted with accidental sampling technique . Respondents in this study are determined based on the opinions Roscoe , as many as 150. Regression analysis was used to test the influence of the independent variables of the study ( cultural , social , personal , and psychological ) on the dependent variable of the study ( purchase decisions) .The results of this study indicate that the culture, social, personal, and psychology influence simultaneously and partially to the decision of tourists visit the Museum Angkut, Kota Batu. Dominant effect is a psychological variable with the value of the beta coefficient of 0.330. Therefore, it is important for marketers to pay attention to the factors that affect consumer behavior such as cultural, social, personal, and psychology factors are less able to be controlled by marketers, but it should be known and taken into consideration for value creation and delivery of products to consumers .Keywords : Cultural, Social, Personal, and Psychological.